Experimental sleep fragmentation and sleep deprivation in rats increases exploration in an open field test of anxiety while increasing plasma corticosterone levels - Tartar, Jaime L. (2008)
Sleep deprivation alters mood and anxiety in man. In rats, 24 h of treadmill-induced total sleep deprivation or sleep fragmentation increased exploratory behavior in an open field test of anxiety compared to cage or exercise controls. Plasma corticosterone (CORT) levels of sleep disturbed and exercise control rats were elevated compared to cage controls, suggesting that the increased exploration observed in the sleep disturbed rats was not due to a hypothalamic–pituitary–adrenal (HPA) stress response.